The Health-Seeking Behavior of Diabetes Mellitus Patients during the COVID-19 Pandemic in Brebes Regency - Hiro Putra Faisal; Chrestella Adiyatma; Dwi Tyastuti (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2022)
Background: The COVID-19 pandemic in Indonesia has impacted patients with non-communicable diseases such as Diabetes Mellitus (DM). The impacts include health services, treatment management, and patients' health-seeking behavior. This study aims to determine the DM patients' health-seeking behavior in the Salem sub-district, Brebes district, Central Java.Methods: This research was a qualitative descriptive study conducted cross-sectionally using a survey. The purposive sampling technique was employed to obtain the data with a total sample of 106 respondents.Results: Most DM patients still visited health facilities during the pandemic (73%). Some efforts to control DM were regularly taking medication (27.7%) and maintaining a healthy diet (34%). However, most respondents stated that they have uncontrolled blood glucose levels (54.7%). During the pandemic, respondents communicated with health workers (75.5%), via telephone (64.2%), and through messaging applications (45.3%). In addition, they search information, especially when they felt symptoms (90.6%), and tried to find information about complications due to the coronavirus (68.9%) with the source from health workers (94.3%). Most respondents had good access (99.1%).Conclusion: The COVID-19 pandemic has resulted changes in DM patients' health-seeking behavior through all aspects. This study shows that most respondents visited health facilities, made efforts to control DM by taking the medication regularly and maintaining a healthy diet, and had high adherence to medication. In addition, respondents had an easy access to health information and communicate with health workers via telephone and messaging applications. The majority of respondents sought information about diabetes and its relationship with COVID-19 during the pandemic.